The Role of Na2CO3 as Precipitating Agent in Salt Purification Process (Future Science)
Salt is an essential compound in life. It is used for food preservation. It is also used for health or isotonic drink, additive in soap production, dialysate, and use an infusion liquid. In the industrial sector, the minimum purity of NaCl in salt was 98.5%. Therefore, the impurities in raw salt from coarse salt should be removed to increase the purity of NaCl and increase the economic value of raw salt. The extraction and recrystallization method can separate the impurities in raw salt by adding the precipitating agent Na2CO3. The mol ratio of Na2CO3 and the stirring time were varied to optimize the weight of Ca extracted and give the high purity. The result showed that using Na2CO3 mol ratio of 1-2.5 will drastically reduce the Ca content (0.03-0.01%) in stirring time 60-150 min. The maximum purity of NaCl obtained from the extraction and recrystallization process was 98.66% using a ratio mol of 1:1 and stirring time of 150 min.